Catheter-associated skin injury: Integration of MARSI principles into vascular access. - Broadhurst, Daphne; Blais, Anne-Marie (Vascular Access)
Skin impairment at vascular access device (VAD) sites presents a significant and multifaceted clinical challenge. To address this, an international consensus panel initiated the development of the first evidence- and consensus-based algorithm for managing skin impairment at VAD sites, now commonly known as catheter-associated skin injury (CASI). Ongoing advancements in CASI science include proposed new classification systems to further refine understanding and guide tailored interventions.